2007
DOI: 10.1002/jsfa.2940
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenolics in sorghum grain on its bitterness, astringency and other sensory properties

Abstract: Despite the fact that condensed tannins are potentially important antioxidants, there is a general belief that tannins in sorghum confer objectionable sensory attributes. The objective of this study was to determine differences in the sensory attributes of sorghums containing different levels of total phenolic compounds. A trained sensory panel described and quantified the sensory attributes of different sorghums (condensed-tannin containing and tannin-free). All the sorghum cultivars were perceived as bitter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 26 publications
4
57
1
Order By: Relevance
“…This fraction also contained significant amounts of bioactive compounds, such as alk(en)ylresorcinols and phenolic acids (Heiniö et al, 2008). In sorghum bitterness and astringency are also caused by phenolic compounds, especially by condensed tannins (Kobue-Lekalake, Taylor & De Kock, 2007;Kobue-Lekalake, 2008). …”
Section: Flavour-active Compounds In Wholegrainsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fraction also contained significant amounts of bioactive compounds, such as alk(en)ylresorcinols and phenolic acids (Heiniö et al, 2008). In sorghum bitterness and astringency are also caused by phenolic compounds, especially by condensed tannins (Kobue-Lekalake, Taylor & De Kock, 2007;Kobue-Lekalake, 2008). …”
Section: Flavour-active Compounds In Wholegrainsmentioning
confidence: 99%
“…However, cooked wholegrain kernels from tannin sorghums having a relatively soft endosperm texture were perceived as dark, hard, chewy, bitter and astringent, while tannin-free sorghums having relatively hard endosperm texture were perceived as soft, sweet and having a maize-like flavour (Kobue-Lekalake, Taylor, & De Kock, 2007). KobueLekalake, Taylor, and De Kock (2009) showed that selection of sorghum cultivars containing low concentration of tannins may both promote health and ensure preference by consumers There seems to be tannin-containing sorghums that are palatable, even to bitter-sensitive consumers, because the tannin levels are below a detection threshold.…”
Section: Breeding or Choice Of Raw Materialsmentioning
confidence: 99%
“…After 14 h of panel training, the sensory evaluation was done in two sessions. The four types of ugali served in transparent glass ramekins were presented using a protocol similar to that of Kobue-Lekalake, Taylor, & De Kock (2007). The panellists handled the ugali with their fingers, the way ugali is normally eaten.…”
Section: Descriptive Sensory Evaluation Of Ugalimentioning
confidence: 99%
“…Traditional sorghum beers are usually produced using brown or red skinned 52 sorghum cultivars (Lyumugabe, Gros, Nzungize, Bajyana, & Thonart, 2012). Use of 53 darker skinned, high tannin cultivars in brewing is thought to result in inhibition of 54 mash enzymes and an objectionable increase in product bitterness (Kobue-Lekalake, 55 Taylor, & de Kock, 2007;Novellie, 1981). However, some workers have suggested 56 that the use of high-tannin sorghum cultivars is responsible for only a minor increase 57 in bitterness, not detectable by all panellists (Daiber, 1975).…”
mentioning
confidence: 99%